2017
DOI: 10.1111/cea.13033
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of low risk of asthma exacerbation during pregnancy

Abstract: Summary Background Assessment of asthma control every 4‐6 weeks during pregnancy is recommended to reduce risk of exacerbation, and by that improve outcome. Objective To identify determinants of pregnancies with low risk of asthma exacerbation. Methods All pregnant women enrolled into the Management of Asthma during Pregnancy (MAP) programme at Hvidovre Hospital since 2007. Assessment of asthma control, adjustment of treatment, spirometry and measurement of exhaled nitric oxide (FENO) were performed, and basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…Data from previous studies suggest that women with asthma may be undertreated during pregnancy. In the study of Ali et al, 41% of pregnant women with asthma were using controller medication pre‐enrolment, and after asthma assessment (including symptoms and lung inflammation measurement) at enrolment, the proportion of women with prescribed controller medication increased to 63%. In agreement, another study found similar increases in ICS prescription rates, with asthma review and management during pregnancy (41% at enrolment, and 69% at end of study) .…”
Section: Discussionmentioning
confidence: 97%
“…Data from previous studies suggest that women with asthma may be undertreated during pregnancy. In the study of Ali et al, 41% of pregnant women with asthma were using controller medication pre‐enrolment, and after asthma assessment (including symptoms and lung inflammation measurement) at enrolment, the proportion of women with prescribed controller medication increased to 63%. In agreement, another study found similar increases in ICS prescription rates, with asthma review and management during pregnancy (41% at enrolment, and 69% at end of study) .…”
Section: Discussionmentioning
confidence: 97%
“…Women with asthma were included in the MAP cohort provided they fulfilled the following criteria: 1) they possessed a diagnosis of asthma as defined according to the GINA-guidelines [10]; 2) they were receiving current prescribed treatment with at least a rescue bronchodilator; and 3) they had their first visit to the respiratory outpatient clinic within the first 18 weeks of pregnancy. A more detailed description of the MAP cohort has been published previously [11][12][13]. Only women from the MAP cohort with a live birth were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Attack of asthma during pregnancy is connected with increased risk of adverse pregnancy and perinatal outcomes. Current studies have shown that acute attack increases the risk of LBW; however, the relationship between acute attack and other adverse outcomes is still controversial, such as PB, SGA, congenital malformations, neonatal death, and hospitalizations, as well as a range of maternal and placental complications, preeclampsia, gestational diabetes, placenta previa, and caesarean section [66,67].…”
Section: Acute Attack Of Asthma In Pregnancymentioning
confidence: 99%